2007
DOI: 10.1002/ijc.22802
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor targets NFκB and TSP1 to suppress prostate tumor growth in vivo

Abstract: The androgen role in the maintenance of prostate epithelium is subject to conflicting opinions. While androgen ablation drives the regression of normal and cancerous prostate, testosterone may cause both proliferation and apoptosis. Several investigators note decreased proliferation and stronger response to chemotherapy of the prostate cancer cells stably expressing androgen receptor (AR), however no mechanistic explanation was offered. In this paper we demonstrate in vivo anti-tumor effect of the AR on prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 70 publications
(64 reference statements)
5
51
0
Order By: Relevance
“…other researchers demonstrated in vivo the antitumor effect of the AR on prostate cancer growth. AR-expressing cells formed tumors in male mice at a much lower rate than the AR-negative controls and, moreover, the AR-expressing tumors showed decreased vascularity and massive apoptosis (45). By immunohistochemistry, we found a greater frequency of nuclear overexpression of AR in normal prostate tissues than in the adenocarcinomas.…”
Section: Discussionmentioning
confidence: 63%
“…other researchers demonstrated in vivo the antitumor effect of the AR on prostate cancer growth. AR-expressing cells formed tumors in male mice at a much lower rate than the AR-negative controls and, moreover, the AR-expressing tumors showed decreased vascularity and massive apoptosis (45). By immunohistochemistry, we found a greater frequency of nuclear overexpression of AR in normal prostate tissues than in the adenocarcinomas.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, when PC-3-v or PC-3-AR9 cells were co-cultured with WMPY1 stromal cells (Webber et al, 1999) and orthotopically transplanted in nude mice, PC-3-AR9 co-cultured cells still produced smaller primary and metastatic tumors than PC-3-v co-cultured cells, suggesting that even in the presence of stromal AR stimulation, the suppressor function of the epithelial AR remains effective. Using transfectants of PC-3 cells with an inducible AR-expressing transgene, Nelius et al (2007) also observed that induction of AR expression in an inducible PC-3-AR þ line resulted in an androgendependent decrease in invasion in vitro and decreased tumorigenecity because of decreased microvascular density that led to increased tumor cell apoptosis after subcutaneous inoculation in nude mice.…”
Section: Pc-3 Cells: Ar Functions As Suppressor Of Proliferation and mentioning
confidence: 96%
“…The interaction between AR and other TFs is much less studied. However, there is growing evidence that AR interacts with other TFs, including AP-1, NF-nB, and Ets family members, and this interaction can modulate activity of those TFs and consequently the transcription of their target genes (3,10,17,18).…”
Section: Introductionmentioning
confidence: 99%